Development of a Local Wisdom Based Entrepreneurship Course Model for Pre-Service Science Teachers to Enhance Entrepreneurial Skills - Sukarno, Sukarno; Haryati, Sri; Amirul, Muhamad Ardi (Journal of Natural Science and Integration, 2025)
This study aimed to design and evaluate a local wisdom–based entrepreneurship course model to enhance the entrepreneurial competencies of pre-service science teachers. The research followed the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) instructional design framework and employed the Delphi and Fuzzy Delphi methods for expert validation involving ten specialists in science and entrepreneurship education. A true experimental design using a posttest-only control group was conducted with 62 participants enrolled in an entrepreneurship course at a university in Central Java, Indonesia. Data were analyzed through descriptive statistics, the Shapiro–Wilk normality test, independent sample t-tests, and Cohen’s d to determine the effect size. The results demonstrated that the developed model achieved high validity across all instructional stages (DV > 0.7; d < 0.2). Empirical findings indicated that the experimental group exhibited significantly higher gains in entrepreneurial skills than the control group (p < 0.05), with a large effect size (Cohen’s d = 2.54). The model effectively strengthened students’ risk-taking abilities, opportunity recognition, self-efficacy, emotional intelligence, and innovative thinking. These findings underscore that integrating local wisdom into entrepreneurship education fosters contextualized learning experiences and promotes sustainable entrepreneurial behavior among future science educators. The proposed model provides a practical framework for higher education institutions to develop entrepreneurial competencies while preserving and utilizing local cultural values.Keywords: entrepreneurship education; local potential; pre-service science teachers; entrepreneurial skills; fuzzy